2012
DOI: 10.1121/1.3662059
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effects of the acoustical conditions in a simulated classroom on speech recognition and learning in children

Abstract: The potential effects of acoustical environment on speech understanding are especially important as children enter school where students' ability to hear and understand complex verbal information is critical to learning. However, this ability is compromised because of widely varied and unfavorable classroom acoustics. The extent to which unfavorable classroom acoustics affect children's performance on longer learning tasks is largely unknown as most research has focused on testing children using words, syllabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
99
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 43 publications
8
99
1
3
Order By: Relevance
“…The simulated acoustic environment consisted of a physical room and a virtually-modeled room (a detailed description of the creation and validation of the environment is presented in Valente et al 2012). In brief, the physical room was fitted with passive acoustical treatments and loudspeakers and LCD monitors on desks were arranged around a child’s location (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulated acoustic environment consisted of a physical room and a virtually-modeled room (a detailed description of the creation and validation of the environment is presented in Valente et al 2012). In brief, the physical room was fitted with passive acoustical treatments and loudspeakers and LCD monitors on desks were arranged around a child’s location (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To address the above issues, a simulated classroom environment was created to examine the effect of acoustic environment (signal to noise ratio (SNR), reverberation time (RT), visual component, talker location) on speech understanding (Valente et al 2012). Valente et al reported results of two experiments conducted to examine simple (sentence repetition) and complex (comprehension) speech understanding tasks in children and adults in this simulated environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation suggested stems from the noise impairment induced on the unique mechanisms underlying the two tasks. A novel paradigm was recently used for tests in a virtual classroom 10 where features of the real environment were taken into closer consideration. This study employed HVAC noise and focused on sentence recognition and classroom learning over a lesson divided into lecture and discussion.…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that listening comprehension using a paper-pencil instructional task was more impaired than speech recognition using a word-to-picture matching task. This is further supported by Valente et al (2012), who also tested four combinations comprised of two SNRs (+7 vs. +10 dB) crossed with two RTs (0.6 vs. 1.5 seconds). Although no direct comparison was made for speech comprehension versus recognition, results showed that the detrimental effect of reverberation and noise was more pronounced in speech comprehension tasks than speech recognition tasks.…”
Section: Introductionmentioning
confidence: 55%